Randomized Trial of 21% versus 100% Oxygen during Chest Compressions Followed by Gradual versus Abrupt Oxygen Titration after Return of Spontaneous Circulation in Neonatal Lambs - Deepika Sankaran; Evan M. Giusto; Amy L. Lesneski; Morgan E. Hardie; Houssam M. Joudi; Emily C. A. Lane; Victoria L. Hammitt; Kirstie C. Tully; Payam Vali; Satyan Lakshminrusimha (MDPI AG, 2023)
The combination of perinatal acidemia with postnatal hyperoxia is associated with a higher incidence of hypoxic-ischemic encephalopathy (HIE) in newborn infants. In neonatal cardiac arrest, current International Liaison Committee on Resuscitation (ILCOR) and Neonatal Resuscitation Program (NRP) guidelines recommend increasing inspired O2 to 100% during chest compressions (CC). Following the return of spontaneous circulation (ROSC), gradual weaning from 100% O2 based on pulse oximetry (SpO2) can be associated with hyperoxia and risk for cerebral tissue injury owing to oxidative stress. We hypothesize that compared to gradual weaning from 100% O2 with titration based on preductal SpO2, abrupt or rapid weaning of inspired O2 to 21% after ROSC or use of 21% O2 during CC followed by upward titration of inspired O2 to achieve target SpO2 after ROSC will limit hyperoxia after ROSC. Nineteen lambs were randomized before delivery and asphyxial arrest was induced by umbilical cord occlusion. There was no difference in oxygenation during chest compressions between the three groups. Gradual weaning of inspired O2 from 100% O2 after ROSC resulted in supraphysiological PaO2 and higher cerebral oxygen delivery compared to 21% O2 during CC or 100% O2 during CC followed by abrupt weaning to 21% O2 after ROSC. The use of 21% O2 during CC was associated with very low PaO2 after ROSC and higher brain tissue lactic acid compared to other groups. Our findings support the current recommendations to use 100% O2 during CC and additionally suggest the benefit of abrupt decrease in inspired oxygen to 21% O2 after ROSC. Clinical studies are warranted to investigate optimal oxygen titration after chest compressions and ROSC during neonatal resuscitation.